2004
DOI: 10.1209/epl/i2004-10214-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling out the density dependence of the α relaxation in glass-forming polymers

Abstract: We show that the density and temperature dependences of the α-relaxation time of several glassforming polymers can be described through a single scaling variable X = e(ρ)/T , where e(ρ) is well fitted by a power law ρ x , x being a species-specific parameter. This implies that "fragility" is an intrinsic, density-independent property of a glassformer characterizing its super-Arrhenius slowing down of relaxations, and it leads us to propose a modification of the celebrated Angell plot.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
247
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(257 citation statements)
references
References 22 publications
9
247
1
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ). [28][29][30] Paper I 1 presented computer simulations of 13 different systems, showing that van der Waals type liquids are strongly correlating, whereas hydrogen-bonding liquids like methanol or water are not.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ). [28][29][30] Paper I 1 presented computer simulations of 13 different systems, showing that van der Waals type liquids are strongly correlating, whereas hydrogen-bonding liquids like methanol or water are not.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 This scenario-scaling of the dynamics, but not the equation of state-is exactly what is experimentally observed for a large number of viscous liquids. For example, in van der Waals liquids relaxation times are found to be a function of n/3 / T ͑using n as an empirical parameter͒, 24,25 but the scaling does not apply to the ͑excess͒ pressure with the exponent determined from the scaling of relaxation time, as required for IPL scaling. 24,26 In Sec.…”
Section: ͑20͒mentioning
confidence: 99%
“…[3][4][5][6]The exponent γ of the thermodynamic scaling also provides a measure of the relative importance of the density and temperature in controlling glassy dynamics. Hence, not surprisingly, a large body of experiments [7][8][9][10][11][12][13] and simulations [14][15][16][17][18][19][20] have probed the nature of thermodynamic scaling of glass-forming liquids since the first observation by Tölle et al for orthoterphenyl. [21] The existence of thermodynamic scaling is well established for as diverse materials as van der Waals liquids, polymers, ionic liquids, weakly hydrogen-bonded systems, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The study is also valuable since the dynamical properties at varying thermodynamic conditions can be predicted from only a few measurements if the material conforms to the thermodynamic scaling. While some have argued that thermodynamic scaling contains little physical content, [9,10] the opposite wide belief is that thermodynamic scaling stems from the nature of the repulsive portion of the intermolecular potential. In fact, the thermodynamic scaling exactly holds for a system interacting with an inverse power law (IPL) potential where γ is indeed determined by the exponent of the power law.…”
Section: Introductionmentioning
confidence: 99%